First teratological case of Pseudomyrmex termitarius (Smith, 1855) (Hymenoptera: Formicidae: Pseudomyrmecinae) - Carreño-Guevara, Yennifer Andrea; Malagón-Aldana, Leonardo; Gamboa, Jean (Acta Biologica Sibirica, 2025)
A case of abnormalities in segmentation (symphysomery) on the metasoma in a worker ant of the species Pseudomyrmex termitarius (Smith, 1855) is described for the first time from Colombia. In the abnormal metasoma, the petiole and postpetiole are fused, and the number of segments of the opisthogaster is reduced. For taxonomic studies, these kinds of abnormalities can generate confusion when identifying individuals at the genus and species levels. For an individual, an anatomical abnormality might affect its biology and interaction with other individuals inside its social insect colony.